2014
DOI: 10.14245/kjs.2014.11.4.245
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Disc Herniation in a Patient With Congenital Vertebral Body Anomaly: A Case Report

Abstract: Lumbar disc herniation is characterized with low back and leg pain resulting from the degenerated lumbar disc compressing the spinal nerve root. The etiology of degenerative spine is related to age, smoking, microtrauma, obesity, disorders of familial collagen structure, occupational and sports-related physical activity. However, disc herniations induced by congenital lumbar vertebral anomalies are rarely seen. Vertebral fusion defect is one of the causes of congenital anomalies. The pathogenesis of embryologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Moreover, repetitive activities that place a significant amount of stress on the lumbar spine, such as gymnastics, dance, and football, can also increase the risk of lumbar disc herniation [13] , [14] , [15] . Also, children born with congenital abnormalities of the spine may be at a higher risk of developing lumbar disc herniation [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, repetitive activities that place a significant amount of stress on the lumbar spine, such as gymnastics, dance, and football, can also increase the risk of lumbar disc herniation [13] , [14] , [15] . Also, children born with congenital abnormalities of the spine may be at a higher risk of developing lumbar disc herniation [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar disc herniation (LDH) is one of the more common spinal diseases caused by the degeneration and the displacement of nucleus pulposus or annulus fibrosis beyond the intervertebral disc space [1]. LDH is characterized with low back and leg pain resulting from the degenerated lumbar disc compressing the spinal nerve root [2]. Many studies have demonstrated that 70–85% of all people will suffer from low back pain at some time in life [3].…”
Section: Introductionmentioning
confidence: 99%
“…Esta etapa consiste en realizar ejercicios de estabilización lumbar, fuerza, de aumento de flexibilidad, combinándolos con ejercicios de tipo aeróbico. Ya que para prevenir o disminuir la hernia lumbar y del sacro es importante fortalecer la zona abdominal y el tono muscular en general (Atabey et al, 2014).…”
Section: Introductionunclassified